Risk factors for recurrent wheezing after bronchiolitis - YH Fan; PL Zhang; YJ Huang; C Xie; T Ai (BMC, 2023)
Abstract Background This study aimed to determine whether there was an association between certain factors in patients with bronchiolitis and recurrent wheezing in childhood. Method In 2021 we tracked children hospitalized for bronchiolitis at Chengdu Women's and Children's Central Hospital in 2017. The patients were classified into recurrent wheezing group (RWG) and non-recurrent wheezing group (NRWG). Possible risk factors including maternal age, school-age siblings, allergic history, atopic dermatitis, allergic rhinitis, atopic family history, severity of the condition, duration of hospitalization, nasopharyngeal secretions culture, blood eosinophil counts, FeNO and skin prick test were compared between the two groups. Continuous variables were analyzed by independent sample t-test for normal distribution and Mann-Whitney U-test for non-normal distribution. Categorical variables were tested using chi-square tests. Multifactor analysis was conducted by stepwise logistics regression analysis. Results In total 167 participants were included, of which 26 and 141 were in RWG and NRWG respectively. In RWG children represented higher maternal age (P = 0.02) and greater probability of allergic history, atopic dermatitis, allergic rhinitis, atopic family history (odds ratio [OR] = 4.0,3.7, 7.8, 10.9 respectively, P < 0.01). However, school-age siblings, severity of the condition, duration of hospitalization, blood eosinophil counts, fractional exhaled nitric oxide and skin prick test results seemed unrelated to recurrent wheezing. In the subgroup analysis of nasopharyngeal secretion culture, there were more Moraxella catarrhalis-positive in RWG(P = 0.043). Atopic dermatitis, allergic rhinitis and atopic family history were identified as independent risk factors for recurrent wheezing. Conclusion Some children with bronchiolitis will develop recurrent wheezing, and the risk factors are allergic history, Moraxella catarrhalis infection or colonization, atopic dermatitis, allergic rhinitis and atopic family history; the latter three are independent risk factors.